Non-Muslim Leadership in The Qur’an: An Integrated Approach Through Shahrur’s Linguistic Analysis And Fazlur Rahman’s Ideal Moral Hermeneutics - Ainiyatul Latifah; Muhammad Hayyi' Lana Alkhan; Srimaharani Tanjung; Akhmad Roja Badrus Zaman; Abd Qowi Azzikri (Jurnal Kawakib, 2026)
The debate over the permissibility of non-Muslim leadership in Muslim-majority societies remains one of the most contested issues in contemporary Islamic political thought. Most classical scholars cite Qur’anic verses, particularly al-Ma’idah (5):51, as absolute prohibitions. This article reexamines those verses through an integrated hermeneutical method that combines Muhammad Shahrur’s structural-linguistic analysis (including his theory of hudud and his rejection of synonymy in Qur’anic Arabic) with Fazlur Rahman’s double movement theory, which foregrounds socio-historical context to extract the ideal moral objectives of revelation. Employing a qualitative-library approach, the study finds that the term awliya’ in al-Ma’idah (5):51 operates within a context of wartime betrayal rather than constituting a blanket prohibition against non-Muslim political leadership. Shahrur’s linguistic method establishes a semantic boundary (hadd) that ranges from ‘loyal ally’ at its minimum to ‘leader’ at its maximum. At the same time, Rahman’s double movement identifies the verse’s ideal moral as the imperative of justice, trustworthiness, and the protection of communal integrity. The integrated reading concludes that al-Ma’idah (5):51 is contextually bounded it targets specific actors who actively betrayed the nascent Islamic polity, not non-Muslims as a permanent legal category. The ideal moral principle that emerges is that leadership must be entrusted to those who are just, capable, and committed to the public good, irrespective of religious affiliation, in contexts of civic pluralism.